Educational Interpreting for Deaf Students Report of the National Task Force on Educational Interpreting - Rochester Inst. of Technology, NY. National Technical Inst. for the Deaf.; Stuckless, E. Ross; Rochester Inst. of Technology, NY. National Technical Inst. for the Deaf. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1989)
This report is intended to stimulate initiatives on the part of governmental, professional, and consumer organizations and institutions that prepare educational interpreters who work with deaf students. Following an introductory chapter on the development of educational interpreting for deaf students, other chapters discuss: (1) job titles and descriptions; (2) roles and responsibilities of educational interpreters and special ethical considerations involved in interpreting; (3) process of hiring an educational interpreter; (4) working conditions for educational interpreters; (5) preparation of educational interpreters, with a suggested curriculum; (6) certification; and (7) training students, parents, teachers, administrators, and elected officials on making effective use of educational interpreting services. Appendixes list 23 selected materials for consumer education; offer a sample job description; list interpreter preparation programs in the United States and Canada; list interpreter service organizations; and outline attitudes, knowledge, and skills conducive to success as an educational interpreter. (JDD)
Availability: Rochester Institute of Technology, Campus Connections, P.O. Box 9887, Rochester, NY 14623-0887 ($10.00).
Policymakers.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Certification; Consumer Education; Deaf Interpreting; Deafness; Elementary Secondary Education; Employment Qualifications; Ethics; Interpreters; Occupational Information; Personnel Selection; Policy Formation; Program Development; Sign Language; Staff Role; Work Environment; Reports, Descriptive; Guides, Non-Classroom.